Conceptualizing the landscape of digital health entrepreneurship: a systematic review and research agenda - Sascha Noel Weimar; Rahel Sophie Martjan; Orestis Terzidis (Management Review Quarterly, 2024)
Digital health, which encompasses the use of digital technology to enhance and support healthcare, can potentially transform the healthcare industry. As healthcare systems struggle to provide high-quality care, entrepreneurs and startups have turned to digital health technology to create innovative products and services that aim at improving healthcare outcomes and reducing costs. This has made digital health entrepreneurship a major driving force for achieving good health and high-quality care. The study aims to analyze the current state of research in digital health entrepreneurship by identifying contributing disciplines and common research themes. A comprehensive literature review based on state-of-the-art definitions of digital health entrepreneurship was conducted to achieve this goal. A total of 164 articles met the final inclusion criteria, and the subsequent inductive analysis revealed the presence of three contributing disciplines and ten distinct themes: Academia Transfer and Education, Ecosystem and Stakeholder, Product and Business Development, Business Model, Classification, Management and Strategy, Regulation, Digital Technology, Implementation and Adoption, and Evaluation. These themes were organized into a conceptual framework depicting the internal and external building blocks of digital health entrepreneurship. The review highlights the importance of a structured understanding of the industry, including its business models and regulatory environment, as well as the role of the various healthcare stakeholders. This analysis can guide researchers and entrepreneurs seeking to navigate the digital health landscape and proposes further research avenues.
Keywords: I10; K23; M13; 650; Digital health; Telehealth; eHealth; Startup; Entrepreneurship; Innovation